A revision of Tetrastigma (Miq.) Planch. (Vitaceae) in Sarawak, Borneo - Wan Nuur Fatiha, Wan Zakaria; Aida Shafreena, Ahmad Puad; Ramlah, Zainudin; Abdul, Latiff (Malaysian Nature Society, 2017)
A revision of the genus Tetrastigma (Miq.) Planch. in Sarawak is presented. A total of 11 Tetrastigma species in Sarawak are recorded namely T. brunneum Merrill, T. dichotomum (Blume) Planch., T. diepenhorstii (Miq.) Latiff, T. dubium (Laws.) Planch., T. glabratum (Blume) Planch., T. hookeri (Lawson) Planch., T. megacarpum Latiff, T. papillosum (Blume) Planch., T. pedunculare (Wall. ex Laws.) Planch., T. rafflesiae (Miq.) Planch., and T. tetragynum Planch. Morphological descriptions are given for each taxon, as well as a key for identification. A general discussion on the growth habits and morphology of stem, inflorescence, flowers, fruits and seeds is also given.